2017
DOI: 10.1080/0163853x.2017.1332446
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Social Networks from Language Statistics

Abstract: Knowledge regarding social information is commonly believed to be derived from sources such as formal relationships and interviews and can be plotted as complex networks. We explored whether social networks can also be extracted through other means by using language statistics. In three computational studies we computed first-order and higher-order (latent semantic analysis) co-occurrences of story characters in three novels. These statistical linguistic frequencies entered in a multidimensional scaling analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…Other proposals argue that the meaning of proper names is determined socially (Jeshion, 2009 ). Neither type of information is easy to extract from text alone, although much research on multimodal models can be seen as providing a framework for the direct reference issue (Bruni et al, 2014 ), and selected types of text, such as social media posts and novels, may provide enough data for the extraction of social networks from word distributions (Dunbar et al, 2015 ; Hutchinson and Louwerse, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other proposals argue that the meaning of proper names is determined socially (Jeshion, 2009 ). Neither type of information is easy to extract from text alone, although much research on multimodal models can be seen as providing a framework for the direct reference issue (Bruni et al, 2014 ), and selected types of text, such as social media posts and novels, may provide enough data for the extraction of social networks from word distributions (Dunbar et al, 2015 ; Hutchinson and Louwerse, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Louwerse and Zwaan (2009) demonstrated that LSA predicted the geographic location and population size of the 50 largest cities in the United States, and its accuracy was on a par with human prediction. Hutchinson and Louwerse (2018) reported that social relationships between fictional characters in three novels could be derived from language statistics. Furthermore, social or cultural biases toward gender or race (e.g., European‐Americans are pleasant vs. African‐Americans are unpleasant) that result in prejudiced decisions have recently been found to be encoded in word vectors (e.g., Bolukbasi, Chang, Zou, Saligrama, & Kalai, 2016; Caliskan, Bryson, & Narayanan, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Despite the fact that an extensive number of studies have applied word vectors to a variety of tasks in many research fields, relatively little effort has been made to explore what type of information or knowledge is encoded in word vectors. Previous studies that have addressed this question have demonstrated that text‐based word vectors reflect perceptual (Louwerse & Connell, 2011; Riordan & Jones, 2011), emotional (Passaro, Bondielli, & Lenci, 2017; Recchia & Louwerse, 2015; Tillmand & Louwerse, 2018), and social (Hutchinson & Louwerse, 2018) information. Although these studies have focused on specific information, some recent studies (Grand, Blank, Pereira, & Fedorenko, 2018; Sommerauer & Fokkens, 2018) have compared various types of knowledge in terms of the representational ability of word vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Some exceptions are Herbelot (2015), which analyzes the properties of distributional representations of person names extracted from novels; work on extracting entity attributes (Gupta et al. 2015; Guu, Miller, & Liang 2015; Hutchinson & Louwerse 2018; Louwerse & Zwaan 2009); building entity representations from annotations and knowledge bases (Bianchi & Palmonari 2017); and the relation between entities and the categories that they instantiate (i.e., instantiation, Boleda, Gupta, & Padó 2017).…”
Section: Introductionmentioning
confidence: 99%